Reduced fecal short‐chain fatty acids in hispanic children with ulcerative colitis. Issue 14 (18th July 2021) - Rotondo‐Trivette, Sarah; Wang, Beibei; Luan, Yihui; Fiehn, Oliver; Sun, Fengzhu; Michail, Sonia
Abstract: Background: It is known that patients with ulcerative colitis (UC) have reduced numbers of short‐chain fatty acid (SCFA) producing bacteria and reduced SCFA concentration in feces. There is also evidence that Hispanic patients have increased incidence of UC and increased likelihood of developing disease at a younger age. To understand why this might be, we compared fiber intake and fecal SCFA concentrations in Hispanic children with UC and non‐Hispanic children with UC. Methods: In this cross‐sectional study conducted at the Children's Hospital of Los Angeles, stool was collected from 22 Hispanic and 31 non‐Hispanic children with UC. SCFAs in the stool were quantified using mass spectrometry. Diet information was collected at the time of stool collection using food frequency questionnaires. Results: Acetic acid, butyric acid, isovaleric acid, and propionic acid concentrations are significantly lower in Hispanic children with UC compared to age, gender, and disease activity matched non‐Hispanic children with UC ( p < 0.001). Butyric acid showed the most significant decrease ( p = 1.6e‐7) There was no significant difference in fiber intake between Hispanic and non‐Hispanic children with UC. Conclusion: To our knowledge, this is the first study to find that Hispanic children with UC had further reduced SCFAs, independent of disease activity and fiber intake. It is possible that the reduction in SCFAs is related to the colonic disease in Hispanic patients with UC. This may provide more evidence to support the use of SCFA targeted therapies for UC. Abstract : Hispanic children with ulcerative colitis have lower short chain fatty acids.